Pharmacological Management of Cardiorenal Syndromes - Andrew A. House; Mikko Haapio; Johan Lassus; Rinaldo Bellomo; Claudio Ronco (International Journal of Nephrology)
Cardiorenal syndromes are disorders of the heart and kidneys whereby acute or chronic dysfunction in one organ may induce acute or chronic dysfunction of the other. The pharmacological management of Cardiorenal syndromes may be complicated by unanticipated or unintended effects of agents targeting one organ on the other. Hence, a thorough understanding of the pathophysiology of these disorders is paramount. The treatment of cardiovascular diseases and risk factors may affect renal function and modify the progression of renal injury. Likewise, management of renal disease and associated complications can influence heart function or influence cardiovascular risk. In this paper, an overview of pharmacological management of acute and chronic Cardiorenal Syndromes is presented, and the need for high-quality future studies in this field is highlighted.